Effective Graphics in Structures Class: Integrating Structures into Architecture - Dytoc, Bronne C. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 3, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} This paper focuses on alternative teaching methods of illustrating structural behavior and concepts for integration into architectural design thinking. To reach this state, the pedagogic gap between architectural and structural classes needs to be bridged. The teaching methods are based on two viewpoints: 1) To comprehend structures in a graphical manner, and 2) To understand structures as a potent sculptor of form. Keys to effectively teaching structures to an architectural class are to communicate with graphics, drawings, demonstration models, and familiar language. These keys are employed for topics such as stress-strain, shear-moment diagrams, beam-column shapes, Maxwell truss diagrams, Polygonal Force diagrams for profiles of arches and cables. Use of well-known examples from daily life further clarify and demystify structures, integrating it into architectural language and experience. Subsequent computations follow to appreciate comparative solutions, and material and construction issues. The formulae variables are recognized as tools for shaping structural-architectural elements. Furthermore, architectural cases are analyzed in a series of slide lectures, revealing the variety of dynamic forms generated from structural issues. Finally, bridge or tower models are built and tested to realize the three-dimensional aspect of structural behavior. To help validate these methods and ideas to the reader, the paper shall be more graphical than textual. The effectivity of these alternative methods are manifested in projects of later design studios, and are also noted in student evaluations of the structural class.